Complex Movements, Philopatry and Expanded Depth Range of a Severely Threatened Pelagic Shark, the Oceanic Whitetip (Carcharhinus longimanus) in the Western North Atlantic - Howey-Jordan, Lucy A.; Brooks, Edward J.; Abercrombie, Debra L.; Jordan, Lance K. B.; Brooks, Annabelle; Williams, Sean; Gospodarczyk, Emily; Chapman, Demian D. (PloS one, 2013)
Oceanic whitetip sharks (Carcharhinus longimanus) have recently been targeted for conservation in the western North Atlantic following severe declines in abundance. Pop-up satellite archival tags were applied to 11 mature oceanic whitetips (10 females, 1 male) near Cat Island in the central Bahamas 1-8 May 2011 to provide information about the horizontal and vertical movements of this species. Another large female was opportunistically tagged in the U.S. Exclusive Economic Zone (EEZ). Data from 1,563 total tracking days and 1,142,598 combined depth and temperature readings were obtained. Sharks tagged at Cat Island stayed within 500 km of the tagging site for ~30 days before dispersing across 16,422 km(2) of the western North Atlantic. Maximum individual displacement from the tagging site ranged from 290-1940 km after times at liberty from 30-245 days, with individuals moving to several different destinations (the northern Lesser Antilles, the northern Bahamas, and north of the Windward Passage). Many sharks returned to The Bahamas after ~150 days. Estimated residency times within The Bahamas EEZ, where longlining and commercial trade of sharks is illegal, were generally high (mean = 68.2% of time). Sharks spent 99.7% of their time shallower than 200 m and did not exhibit differences in day and night mean depths. There was a positive correlation between daily sea surface temperature and mean depth occupied, suggesting possible behavioral thermoregulation. All individuals made short duration (mean = 13.06 minutes) dives into the mesopelagic zone (down to 1082 m and 7.75°C), which occurred significantly more often at night. Ascent rates during these dives were significantly slower than descent rates, suggesting that these dives are for foraging. The sharks tracked appear to be most vulnerable to pelagic fishing gear deployed from 0-125 m depths, which they may encounter from June to October after leaving the protected waters of The Bahamas EEZ.